2016
DOI: 10.1128/jvi.03073-15
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus E2 Regulates SRSF3 (SRp20) To Promote Capsid Protein Expression in Infected Differentiated Keratinocytes

Abstract: The human papillomavirus (HPV) life cycle is tightly linked to differentiation of the infected epithelial cell, suggesting a sophisticated interplay between host cell metabolism and virus replication. Previously, we demonstrated in differentiated keratinocytes in vitro and in vivo that HPV type 16 (HPV16) infection caused increased levels of the cellular SR splicing factors (SRSFs) SRSF1 (ASF/SF2), SRSF2 (SC35), and SRSF3 (SRp20). Moreover, the viral E2 transcription and replication factor that is expressed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 55 publications
(96 reference statements)
1
58
0
Order By: Relevance
“…Specifically, HPV16 and HPV31 E2 can transcriptionally upregulate the expression of at least SRSF1, -2, and -3 ( Fig. 1D) (31). This exciting finding implies that because the relative levels of SRSFs in a cell determine alternative splicing outcomes and thus the overall protein profile, E2 may control the cellular environment via control of SRSF expression to optimize viral replication.…”
Section: E2 As a Regulator Of Srsfsmentioning
confidence: 82%
“…Specifically, HPV16 and HPV31 E2 can transcriptionally upregulate the expression of at least SRSF1, -2, and -3 ( Fig. 1D) (31). This exciting finding implies that because the relative levels of SRSFs in a cell determine alternative splicing outcomes and thus the overall protein profile, E2 may control the cellular environment via control of SRSF expression to optimize viral replication.…”
Section: E2 As a Regulator Of Srsfsmentioning
confidence: 82%
“…This suggests that although the late region can be transcribed in less differentiated cells, RNA processing or export from the nucleus is inhibited, or cytoplasmic late mRNAs are highly unstable. Late pre-mRNAs may be synthesised in less differentiated keratinocytes, at least in the W12 and NIKS16 models of the virus life cycle, because it is possible to induce L1 protein expression by manipulating levels of certain RNA-binding proteins [ 92 , 98 ]. Moreover, expression of reporter constructs containing the entire wild type HPV16 late regulatory element gave significantly increased RNA nuclear retention compared to similar constructs with mutations affecting key protein-binding regions of the element [ 97 ].…”
Section: Differentiation-dependent Regulation Of Polyadenylationmentioning
confidence: 99%
“…In general, cellular and viral splicing is positively controlled by SR splicing factors [ 108 ], and negatively by hnRNP proteins [ 109 , 110 ]. HPV controls expression of SRSF1, 2 and 3 through the viral E2 transcription factor [ 98 ] and SRSF levels peak in the mid to upper layers of HPV-infected epithelial [ 75 , 98 ] where late gene expression commences [ 23 ], and E2 is most highly expressed [ 32 , 33 ]. Recently, we reported that SRSF3 controls L1 protein expression in a differentiation-dependent manner.…”
Section: Differentiation-dependent Regulation Of Polyadenylationmentioning
confidence: 99%
“…However, to date only a limited number of genes are validated to be regulated by E2. These include MMP-9 (Behren et al, 2005), hTERT (Lee et al, 2002), SF2/ASF (Klymenko et al, 2016; Mole et al, 2009), IL-10 (Bermudez-Morales et al, 2011), p21 (Steger et al, 2002), involucrin (Hadaschik et al, 2003), ÎČ 4-integrin (Oldak et al, 2010) and most recently c-Fos (Delcuratolo et al, 2016). Brd4 is necessary for E2’s function as a transcriptional activator when E2BS is positioned away from the promoter-proximal region in an enhancer-like sequence context (Lee and Chiang, 2009) as found in CRPV (see Fig.…”
Section: Brd4 and E2 In The Regulation Of Cellular Genes And Theirmentioning
confidence: 99%